Mapping knowledge structures and trends on walkability studies - Linda Hijriyah; Anuar Alias; Mohd Firrdhaus Mohd-Sahabuddin (Penerbit Universiti Kebangsaan Malaysia, 2024)
Walkability is a significant and well-known study to make the built environment to be walkable. However, there is a scarcity of material that aims to investigate the structure and research trends of walkability in recent years. Therefore, the objective of this systematic review is to investigate the structure and research trends in walkability. By applying the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) review method, a systematic literature review (SLR) identifies 50 studies by walkability from 2021 to 2022 from the 3 well-known databases for searching scientific publications including Web of Science, Scopus, and Sage. A mapping technique using VOSviewer to identify thematic focus is employed. Based on these 50 studies, it shows that the existing research on walkability within two years consists of some conceptual aspects that underlying walkability studies including ‘the built environment’, ‘walking’ and physical activity’, which then leads to one or some specific problems on physical or perceived factors which ultimately aim to create a walkable area. Hence, it is significant to do more research on the integration between factors in this field to solve the dependence on motorized transportation for future scholarly work. In addition, the usage of tools could enrich the existing literature on this field. It is also noted that various age perceptions to solve walkability issues need to be considered. The research also emphasizes significant authors, journals, references, countries, and organizations that have contributed to the development of the walkability literature to elaborate in more detail on thematic focus.